2017
DOI: 10.1177/2158244017706710
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Solutions: The Experiences of Newly Qualified Science Teachers

Abstract: Some of the challenges cut across subject areas, others are peculiar to the school, and others are peculiar to the individual.The literature abounds in studies that have been done to find the challenges of NQTs but few studies have been done on NQTs who teach science, and almost all the studies have been done in the more developed countries. Generally, these studies are deficient in focusing on the solutions that the NQTs have applied to their situations. This study enriches the literature in this area by focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 9 publications
2
26
0
Order By: Relevance
“…This finding is also confirmed by Boakye and Ampiah (2017), who found that students were handicapped because of their inadequate knowledge of the English language and because they did not have the basic knowledge expected of them. In the Indonesian context, this finding is also similar to what Sayuri (2016) found in fresh pre-service teachers.…”
Section: Students' Interests and Ability In Englishsupporting
confidence: 63%
See 1 more Smart Citation
“…This finding is also confirmed by Boakye and Ampiah (2017), who found that students were handicapped because of their inadequate knowledge of the English language and because they did not have the basic knowledge expected of them. In the Indonesian context, this finding is also similar to what Sayuri (2016) found in fresh pre-service teachers.…”
Section: Students' Interests and Ability In Englishsupporting
confidence: 63%
“…This study has indicated that the teachers generally used various teaching strategies to deal with their problems in teaching English at remote secondary schools in Indonesia (Boakye & Ampiah, 2017;He & Cooper, 2011). They also employed diverse learning resources to cope with the limited support for teaching and learning in their schools, particularly for their professional development.…”
Section: Coping With the Curriculum Dilemmamentioning
confidence: 99%
“…Keengwe et al (2016) indicated that there was a gap between the program of study provided to trainee teachers and the reality existing in schools such as inadequate teaching skills and learning materials. Boakye and Ampiah (2017) indicated that newly qualified teachers had low selfefficacy and inadequate knowledge and skills. Such a deficit needs to be addressed (Ulla, 2017).…”
Section: Problem Statementmentioning
confidence: 99%
“…Besides that, other teachers especially those teaching science subjects also faced a lot of challenges in classroom teaching such as (i) lack of resources for teaching and learning, (ii) time management especially to finish the syllabus and achieve lesson objectives, (iii) deficiency in content knowledge, (iv) inability of students to understand the lesson taught, (v) student's discipline in classroom, (vi) lack of student interest in subject matter, and (vii) inability to complete the integrated syllabus of the subjects (Boakye & Ampiah, 2017). Generally, from all of the above reviews, it is possible to conclude that teachers face a lot of problems and challenges in teaching and learning; and at the same time they still do not have the best model to guide them.…”
Section: Introductionmentioning
confidence: 99%